Edukasi Pemeriksaan Mammography untuk Screening Kanker Payudara pada Ibu PKK di Deda Sudimara Kecamatan Cilongok - Ananda Riski Catur Pamungkas; Atun Raudatul Ma’rifah; Siti Haniyah (Pusat Riset dan Inovasi Nasional, 2025)
Breast cancer is one of the major public health problems in Indonesia, with incidence rates continuing to rise each year, including in Banyumas Regency. A preliminary survey conducted in Sudimara Village, Cilongok District, recorded 13 cases of breast cancer during the 2022–2024 period. However, the level of knowledge among community members, particularly PKK women’s groups, regarding early detection of breast cancer through mammography remains relatively low. This situation indicates the need for structured educational interventions to improve awareness and understanding. This Community Service Program (PkM) was aimed at increasing the knowledge of PKK women about the importance of mammography as an early breast cancer screening effort. The program was implemented through two sessions consisting of several activities, including a pre-test, interactive lectures, group discussions, educational video screenings, leaflet distribution, and a post-test to evaluate the effectiveness of the intervention. Out of 30 registered participants, 24 fully attended all sessions until the final stage. The pre-test results showed an average knowledge score of 53, with the majority of participants (62.5%) categorized as having low knowledge. After the educational sessions, the average post-test score increased significantly to 88, with most participants (87.5%) classified as having good knowledge. These findings confirm that health education using participatory approaches and varied media is effective in improving PKK women’s knowledge of early breast cancer detection. Furthermore, this activity provides practical evidence that community-based educational interventions can serve as a strategic model for empowering women’s groups to support breast cancer prevention efforts at the community level.